2016
DOI: 10.1080/19491034.2016.1238997
|View full text |Cite
|
Sign up to set email alerts
|

The selective permeability barrier in the nuclear pore complex

Abstract: The nuclear pore complex (NPC) mediates the shuttle transport of macromolecules between the nucleus and cytoplasm in eukaryotic cells. The permeability barrier formed by intrinsically disordered phenylalanine-glycine-rich nucleoporins (FG-Nups) in the NPC functions as the critical selective control for nucleocytoplasmic transport. Signal-independent small molecules (< 40 kDa) passively diffuse through the pore, but passage of large cargo molecules is inhibited unless they are chaperoned by nuclear transport re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 79 publications
(186 reference statements)
0
56
0
Order By: Relevance
“…NPCs are ~60 to 120 MDa structures involved in the trafficking of macromolecules between the nucleus and the cytoplasm that are composed of at least 30 different Nups . These include the transmembrane Nups (POMs) that anchor to the NPC in the nuclear envelope, structural Nups that form the skeleton of the NPC, and the intrinsically disordered Nups that constitute the permeability barrier with their disordered phenylalanine‐glycine‐rich regions (FG‐Nups).…”
Section: Introductionmentioning
confidence: 99%
“…NPCs are ~60 to 120 MDa structures involved in the trafficking of macromolecules between the nucleus and the cytoplasm that are composed of at least 30 different Nups . These include the transmembrane Nups (POMs) that anchor to the NPC in the nuclear envelope, structural Nups that form the skeleton of the NPC, and the intrinsically disordered Nups that constitute the permeability barrier with their disordered phenylalanine‐glycine‐rich regions (FG‐Nups).…”
Section: Introductionmentioning
confidence: 99%
“…These channels are occupied by nuclear pore complexes (NPCs), massive multiprotein assemblies that regulate the back and forth movement of macromolecules across the NE. 2 As with the NE as a whole, NPCs are also highly conserved. Electron microscopic studies have revealed a core structure displaying eightfold radial symmetry.…”
mentioning
confidence: 99%
“…RanGap1, an NPC binding protein with known roles in nucleocytoplasmic transport, was also found to have increased expression after injury. Expression of the nucleoporins surprisingly shifted from the classical perinuclear pattern to an intranuclear pattern [80]. The expression pattern of other nucleoporins was not examined and these experiments are still preliminary, but the possible role of nucleoporins in the resolution or pathology of brain injuries is exciting.…”
Section: Npcs In Neurological Disorders and The Aging Brainmentioning
confidence: 99%